Outcome of sentinel lymph node biopsy in patients with clinically non-metastatic renal cell carcinoma. (2nd November 2018) - Kuusk, Teele; De Bruijn, Roderick; Brouwer, Oscar R; De Jong, Jeroen; Donswijk, Maarten; Hendricksen, Kees; Horenblas, Simon; Jóźwiak, Katarzyna; Prevoo, Warner; Valdés Olmos, Renato A; Van Der Poel, Henk G; Van Rhijn, Bas WG; et al.
Abstract: Objective: To investigate the rate of occult SN metastases, oncological outcome, and association of recurrence with the pattern of lymphatic tumour drainage in RCC. Materials and methods: A pooled RCC sub-group analysis was conducted of secondary endpoints from a published feasibility and a phase II prospective single-arm SN study to investigate oncological outcome. Patients with cT1-3 (<10 cm) cN0M0 RCC of any sub-type were enrolled. After intratumoural injection of Tc 99m nanocolloid, pre-operative imaging of SNs with SPECT/CT was followed by (partial) nephrectomy with SN and regional lymph node dissection using a γ -probe. The patients were followed with a risk-adapted surveillance programme. Endpoints of the studies were analysed using Cox proportional hazard models. Results: Sixty-six RCC patients were included. Two patients (3%, 95% CI =0.5–11%) had occult SN metastases and remained free of disease at 57 and 72 months. Ten patients (15%, 95% CI =7–26%) developed recurrences, and four (6%, 95% CI =2.3–14.5%) had died of disease at a median follow-up of 57 months (IQR =18–72 months). Occurrence of distant metachronous metastases were associated with tumour size (HR =1.39, p  = 0.02), pT stage (HR =6.83, p  < 0.01 for comparison T1 vs T3/4), Grade 3/4 (HR =8.38, p  = 0.05 for comparison 1/2 vs 3/4) and interaortocaval sentinel lymph node location (HR =10.52, p  = 0.03 for comparison yes vs no). Conclusions: The rate of occult metastatic SN is low, but long disease-free survival (DFS) was observed in two patients with occult SN metastases. We hypothesize an interaortocaval lymphatic route in thoracic recurrences. Evaluation of the prognostic and therapeutic role of sentinel lymph node biopsy (SLNB) requires a clinical trial in high-risk RCC.